THE POLITICAL ECONOMY OF DROUGHT AND THE MARGINALISATION OF THE POOR - Rao, C. Srinivasa (International Journal of Research -GRANTHAALAYAH, 2022)
The general theme of this paper is that drought, though an agro-climatic phenomenon, has phenomenon has far reaching socio-economic consequences. The adverse impact of drought on the poorer sections is devastating, while the richer classes may actually benefit from it. There actually may emerge a emerge, a new middle class consisting of the middle peasantry, rich families and traders in the countryside and a section engaged in urban based trading, industrial and services sector.